"@ me if you need shoutout": Exploring Women's Roles in Islamic State Twitter Networks. (4th May 2019) - Huey, Laura; Inch, Rachel; Peladeau, Hillary
ABSTRACT: This article investigates the social media content of women who are affiliated with the Islamic State. Throughout one year, ninety-three Twitter accounts were tracked to explore the patterns of engagement by pro–Islamic State women online and examine how these patterns illuminate the roles that pro–Islamic State women occupy on social media networks. The study reveals that women who associate with the Islamic State mostly preserve the traditional gendered role of support in the online realm. However, support is not their exclusive role and some women are active in the organization, using Twitter to recruit, promote, and even commit terrorist violence.